PERANCANGAN MULTIMEDIA CENTER DI TANGERANG SELATAN - Bayu Hudaya; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Abstract Multimedia Center is an integrated place or center that accommodates several activities and learning related to Multimedia devices, a place that can accommodate various activities of technology lovers and is able to meet the needs of the community for information about technology that is developing at this time. In addition, it is also equipped with a seminar venue and other supporting facilities. Multimedia Center also acts as a center or information center of technology in the world that is currently trending. This place is aimed at the general public from all walks of life, ranging from children to adults. High-Tech Architecture is the design style of a building or built environment with certain standards which are then arranged and arranged so that the solution of existing problems is successfully achieved by the use of functional and aesthetic building materials. High-tech is defined as an architectural flow that leads to the idea of a modern architectural movement that exaggerates the impression of the structure and technology of a building. Characteristics that become a reference for high-tech architecture are buildings made from synthetic materials such as metals, glass, and plastics.